Faith and Morality: The Islamic View (American Journal of Islam and Society, 1992)
There is a point of view popular with some religious thinkers-amongthem Muslims-that religion and morality are two separate institutions andhave very little to do with each other. This is because the former is centeredin God, while the latter is entirely human in content and approach. Accordingto this view, an individual can be moral without subscribing to anyrecognizable religion. Furthermore, a deeply religious person occupies a stationin life where usual relations with the world, including those with otherpeople, are perceived as being so lowly and mundane that they become irrelevant.This is, to say the least, not the essential Qur’anic standpoint.The Qur'an , as well as a number of sayings of the Prophet, does not envisagean estrangement between God and humanity. Human beings are said tohave been created after the image of God: Who is nearer to each person thanhisher own jugular vein (Qur'an 50:16). They a so close to each other thatthey may possibly enter into a mutual dialogue. There is thus an organicallyintimate relevance of the individual’s religious faith with the subsequent performanceof the corresponding moral actions. In the Qur’an, the word amanu(they held on to faith [in God]) is almost invariably followed by ‘amilu alsalihat (they performed good actions). However, it must be undelstood thatfaith is not an honorific term, a characteristic that may be inculcated into anperson’s character in its own right. It rather refets to a barely psychologicalstate, an attitude of mind A person may have faith in the all-good God or insome evil being(s) (Qur’an 4:31). In the first case, such an individual isnecessarily good, in the other, he/she is bound to be morally bad ...